A Study of 122 Cases of Pancreatic Cancer Diagnosed by Endoscopic Retrograde Cholangiopancreatography(ERCP) - Moon, Young Myoung (Korean J Intern Med, 1986)
ERCP is a highly accurate and specific method for evaluating patients with suspected pancreatic disease. Its diagnostic significance of specific pancreatographic signs is of even greater importance. We reviewed 122 cases of pancreatic cancer who were done ERCP, at the Department of Internal Medicine, Yonsei University, College of Medicine between June 1973 and August 1983. 1. The ages of 122 patients ranged from 27 to 76 with the majority in the 6th and the 7th decades. The male to female ratio was 2.49:1. 2. The success rate of cannulation into the orifice of the duodenal papilla in 122 cases was 97.5% (119/122), and the pancreatic duct was visualized in 91.0% (111/122). 3. Diagnostic accuracy of ERCP in pancreatic cancer was 96.4% (107/111) among cases in whom the pancreatic duct was visualized. 4. By ERCP the most common site of the lesion was head of pancreas (51.4%). 5. According to Fukumoto’s classification, the most common type was obstructive type (65.4%), followed by the stenosing type (29.0%), abnormal branching type (3.7%), and narrowing type (1.9%). 6. According to Takaki’s classification, Type I (obstruction or stenosis of the main pancreatic duct) was most common (85.6%), followed by Type III (pancreatic dilatation) (9.0%), Type IV (normal pancreatic duct) (3.6%), and Type II (obstruction of Wirsung’s duct or Santorini’s duct) (1.9%). 7. Of the 122 cases of pancreatic cancer, the bile duct was visualized in 55 and abnormalities, such as indentation (32.1%), stenosis (42.9%), and obstruction (25.0%) were found in 28. The locations of abnormal findings in the bile duct were distal (50.0%), middle (46.4%), and proximal (3.6%).